Theory and method in higher education research. Volume 6 - Huisman, Jeroen; Tight, Malcolm (Bingley, U.K. : Emerald Publishing Limited, 2020)
Higher education research is a developing field internationally, which is attracting more and more researchers from a great variety of disciplinary backgrounds within and beyond higher education institutions. As such, it is an arena within which a wide range of theories, methods and methodologies are being applied. This volume of Theory and Method in Higher Education Research contains analyses and discussions of, amongst others, relational working, corpus linguistics, data dialogues, instrumental variables, participatory pedagogy, diverse participation, policy discourse, quality management and knowledge structures of research.
Prelims -- Theorising Practices of Relational Working across the Boundaries of Higher Education -- Uses of Corpus Linguistics in Higher Education Research: An Adjustable Lens -- Dialogues with Data: Generating Theoretical Insights from Research on Practice in Higher Education -- The Use of Instrumental Variables in Higher Education Research -- Participatory Pedagogy and Artful Inquiry: Partners in Researching the Student Experience -- Rolling Out the Mat: A Talanoa on Talanoa as a Higher Education Research Methodology -- Rethinking Diversity: Combining Sen and Bourdieu to Critically Unpack Higher Education Participation and Persistence -- Deleuzian Approaches to Researching Student Experience in Higher Education -- Investigating Policy Processes and Discourses in Higher Education: The Theoretical Complementarities of Bernstein's Pedagogic Device and Critical Discourse Studies -- Framing Theory for Higher Education Research -- Research into Quality Assurance and Quality Management in Higher Education -- Knowledge with Impact in Higher Education Research.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Education, Higher -- Research; Education -- Higher; Higher & further education, tertiary education